Left atrial vascularised thrombus diagnosed by transoesophageal cross sectional echocardiography. Issue 6 (December 1987) - Taams, M A; Gussenhoven, E J; Lancée, C T
Abstract : This report describes a patient with a Björk-Shiley mitral valve prosthesis in whom transoesophageal cross sectional echocardiography revealed a large vascularised mass within the left atrial appendage with smoke-like opacification of blood flow in the left atrium. Transoesophageal cross sectional echocardiography gave a detailed image of the lesion which was unobtainable with precordial cross sectional echocardiography.